Intraocular Pressure in Northern China in an Urban and Rural Population: The Beijing Eye Study - Xu, Liang; Li, Jianjun; Zheng, Yuanyuan; Cui, Tongtong; Zhu, Jianbo; Ma, Ke; Yang, Hua; Ma, Binrong; Jonas, Jost B. (American journal of ophthalmology, 2005)
To evaluate intraocular pressure (IOP) and its demographic associations in an urban and rural population in Northern China. Population-based cohort study. In the Beijing Eye Study, IOP was measured by noncontact pneumatonometry. Mean age was 56.20 ± 10.59 years (range, 40–101 years). Mean IOP was 16.11 ± 3.39 mm Hg (median, 16 mm Hg; range, 7–60 mm Hg). In the rural group and the urban population group, respectively, IOP was significantly ( P = .016 and P = .029, respectively) lower in the high-age group (≥75 years) than in the middle-age group (55–64 years). In the rural group, IOP was additionally significantly lower in the age group of 40 to 44 years than in the middle-age group, which suggests a reversed U-like course. A multiple regression analysis revealed that IOP significantly increased with myopia ( P = .024), and that it was statistically independent of rural area vs urban area ( P = .12) and gender ( P = .71). In the Northern Chinese population, mean and median of IOP that is measured by pneumatonometry is 16 mm Hg with a normal range (mean ± two SDs) of 10 to 22 mm Hg. In cross-sectional analysis, IOP slightly increased towards an age of 55 to 64 years and decreased towards higher ages. IOP increased with myopia. It was not associated with rural vs urban region or gender.